IMPLEMENTASI LOGIKA FUZZY PADA REKOMENDASI PEMILIHAN JURUSAN SISWA BARU: STUDI KASUS : SMK TAMAN SISWA RANCAEKEK - Siti Yuliyanti; Wulan Suryani; Haris Irnawan (LPPM STMIK Bandung, 2020)
Education plays a very important role in improving the quality of human resources. The process of selecting a course for prospective students at SMK Taman Siswa Rancaekek is still done manually. This research aims to analyze new students in determining the majors that match their talents, interests, and abilities. Therefore, the result of this research is the development of a fuzzy logic implementation system using the Tsukamoto method. The research results show that the Tsukamoto method can provide recommendations based on subjects with high values. The system development method used is the Prototype method, with the system design using procedural techniques, while implementation is done using the PHP programming language.